Modular and Formal Design Approach of Industrial Automation using Coloured Petri Net - Panjaitan, Seno Darmawan (Faculty of Engineering, Universitas Tanjungpura, 2008)
Abstract This paper presents the use of Coloured Petri Net (CPN) for modeling and analysis on Automation system. Flexibility and re-configurability are prominent requirements for the current and future automation system. For complex systems, a dominant characteristic is modularity of functional modules. Therefore, a modular approach in building a CPN model is proposed in this paper including its analysis. This aaproach is useful to avoid the construction of a single state space of the entire system and get a simplified model. As an illustration, modeling and state space analysis of the given example by means of CPN is given. Keywords Coloured Petri Net, Modularity, Automation, Scheduling, Verification.